Project Management Maturity Level and PMBOK 7th Recommendations: Case Study of an IT Service Provider Company - Egie, Maria Clara (The Indonesian Journal of Computer Science, 2024)
As a provider of consulting and solutions in the ICT field, PT XYZ has the responsibility to complete projects within budget, on time, and meeting all specified scopes. However, projects from 2022-2023 have experienced delays in completion ranging from 1-6 months from the initial planning. This has resulted in the projects being considered unsuccessful due to these delays. Based on the analysis, there is a need to analyze the project management maturity level in PT XYZ's CRM division. This research aims to measure the project management maturity level and provide recommendations to improve it to the desired level. The maturity level measurement will use the Kerzner Project Management Maturity Model (KPM3). Through the measurement results, it was found that PT XYZ's CRM division has not yet passed the first level. Recommendations have been provided based on KPM3 to progress to the next level. Knowledge area-specific recommendations have also been given based on the 7th edition of PMBOK.